Study Levels of Some Biochemical Parameters in Serum of Pancreatic Cancer Patients - Layla A. Mustafa; Zena A. Mohammad (Tikrit Journal of Pure Science)
This study included an estimation for the levels of some biochemical parameters in the serum of those pancreatic cancer patients, by collecting (40) blood samples from patients their ages ranged (30-70) years compared with (55) blood samples of healthy persons as control group. The parameters included Super oxide dismutase, Amylase, Ribonuclease (acidic and alkaline), Arylesterase, Alkaline phosphatease, Carcinoembryonic antigen, carbohydrate antigen 19-9, Total lipid and Bilirubin Results of the Statistical analysis indicated a significant decrease in the activity of Amylase and Super oxide dismutase patients in comparison with the control group. There was a significant increase in the activity of Ribonuclease (acidic and alkaline), Arylesterase, Alkaline phosphatease, Carcinoembryonic antigen, carbohydrate antigen 19-9, Total lipid and Bilirubin in patients in comparison with the control group.